2010
DOI: 10.3171/2010.7.focus10159
|View full text |Cite
|
Sign up to set email alerts
|

The role of stereotactic radiosurgery in the multimodal management of growth hormone–secreting pituitary adenomas

Abstract: Growth hormone (GH)–secreting pituitary adenomas represent a common source of GH excess in patients with acromegaly. Whereas surgical extirpation of the culprit lesion is considered first-line treatment, as many as 19% of patients develop recurrent symptoms due to regrowth of previously resected adenomatous tissue or to continued growth of the surgically inaccessible tumor. Although medical therapies that suppress GH production can be effective in the management of primary and recurrent acromegaly, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 68 publications
1
25
2
4
Order By: Relevance
“…SRS can be given either by linear accelerator or by cobalt unit (gamma-knife (GK)). The rates of both biochemical and tumor response are very variably reported in the literature: 17-82% and 37-100%, respectively, as reported in a critical analysis of the literature (Stapleton et al 2010). This high variability can be attributed to different treatment schedules, criteria of cure or follow-up durations.…”
Section: Medical Treatmentmentioning
confidence: 89%
See 1 more Smart Citation
“…SRS can be given either by linear accelerator or by cobalt unit (gamma-knife (GK)). The rates of both biochemical and tumor response are very variably reported in the literature: 17-82% and 37-100%, respectively, as reported in a critical analysis of the literature (Stapleton et al 2010). This high variability can be attributed to different treatment schedules, criteria of cure or follow-up durations.…”
Section: Medical Treatmentmentioning
confidence: 89%
“…Prolonged follow-up of patients who underwent stereotactic RT in the last decades will clarify the risks following these procedures. Rare complications of SRS are cranial nerves deficits, headache, radiation necrosis, carotid artery stenosis, and trigeminal neuralgia (Beauregard et al 2003, Stapleton et al 2010. The risk of visual complications limits the use of SRS to lesions more than 3 mm away from the optic structures (Petrovich et al 2003).…”
Section: Medical Treatmentmentioning
confidence: 99%
“…1, Landolt et al 4 ), which is the only consistent predictor of response to radiosurgery. The authors of other studies have reported no difference in response related to medical therapy during radiosurgery, as discussed by Rowland and Aghi 7 and Stapleton et al 8 in this issue of Focus. Whether or not medical therapy during radiation exposure influences tumor response-one benefit of briefly withdrawing medical suppression of GH-producing tumors, as summarized by Rowland and Aghi 7 -it also provides a beginning baseline of GH and insulin-like growth factor-I without the confounding influences of hormonal suppression, for later comparisons; furthermore, unlike prolactin-producing tumors, brief withdrawal of medical therapy is unlikely to result in a rapid rebound of tumor size.…”
Section: Influence Of Medication On Response To Radiosurgerymentioning
confidence: 70%
“…There is, however, no compelling evidence to support this. Loss of pituitary function after either therapy is usually limited to 1 or 2 pituitary functions, rather than panhypopituitarism, and it occurs over several years, accumulating for 10-15 years after treatment, as summarized in the current issue in reports by Stapleton et al 8 and Yang et al 9 Because with radiosurgery we have access to very few studies with follow-up durations beyond 5 years (see the tables in the reports by Rowland et al, 7 Stapleton et al, 8 and Yang et al 9 ), the true incidence of adverse effects on pituitary function over time cannot be known until the data to measure it are available. For instance, in the only radiosurgery series with a minimum median follow-up of 10 years, 6 46% of patients with acromegaly who underwent radiosurgery had endocrine remission at 10 years and 50% developed new anterior pituitary insufficiencies, the majority of which appeared more than 5 years after treatment.…”
Section: Radiosurgery Versus Fractionated Radiation Therapymentioning
confidence: 99%
“…6,7 While radiation can effectively control tumor size in secreting and non-secreting tumors, the results for normalizing hormonal over-production in secreting tumors is variable and generally less effective (15-82%). [8][9][10] In GH-secreting tumors, stereotactic radiosurgery (SRS) normalizes IGF-I levels in approximately 50% of cases. 11,12 In addition, radiation therapy has slow effects, with median endocrine normalization occurring at 6-48 mo, but taking as long as 20 y.…”
Section: Introductionmentioning
confidence: 99%